Synthesis of 3-hexylthiophene derived semiconductor polymers and composites with nanoparticles - Vaquera, Edgar; Caballero, Arturo; Retana, Fernanda; López Cortina, Susana; Serrano, Thelma (Quimica Hoy, 2022)
The monomer 3-hexylthiophen-2,5-dicarboxaldehyde was synthetized from precursor 3-hexylthiophene by VilsmeierHaack reaction. Three p-type semiconductor polymers (PHT-P, PHT-B and PHT-H) were synthetized by aldol condensation from this monomer with three different ketones (propanone, butanone and hexanone). Three composites were created by adding PbS/ZnS nanoparticles to these polymers. Light absorption increased to the red from polymers to composites. Electrical conductivity increased from 10% S/cm in polymers to 10! S/cm in composites.